Comparative evaluation of transmediastinal and minimally invasive McKeown esophagectomy for esophageal cancer: perioperative and oncologic outcomes - Ni, Zhichao; Zhu, Zigui; Shi, Xin; Xia, Xi; Liu, Yan; Cui, YeHua; Zhang, Yi; Zhang, Jianxin (Frontiers in Oncology, 2025)
BackgroundEsophageal squamous cell carcinoma remains a major health burden in China, where surgical resection is the mainstay of curative therapy. The conventional minimally invasive McKeown esophagectomy (MIE-McKeown), although oncologically effective, entails transthoracic access and single-lung ventilation, often resulting in higher postoperative morbidity. Thoraco-laparoscopic transmediastinal esophagectomy has emerged as a novel alternative that may mitigate these risks while preserving oncologic integrity.MethodsA retrospective cohort study was conducted involving 268 patients with resectable middle or lower thoracic esophageal squamous cell carcinoma (clinical stage I–III), including 131 who underwent transmediastinal esophagectomy and 137 who received MIE-McKeown. Outcomes assessed included operative time, intraoperative blood loss, lymph node yield, complication profiles, recovery indicators, quality of life (EORTC QLQ-C30), and 6-month disease-free survival (DFS). Statistical comparisons were performed using t-tests, χ² tests, and multivariate logistic regression.ResultsThe transmediastinal esophagectomy group exhibited significantly shorter operative time (197.2 ± 25.9 vs. 286.5 ± 32.1 min, P<0.001) and reduced blood loss (155.4 ± 40.2 vs. 260.7 ± 65.1 mL, P<0.001). Time to oral intake (4.6 ± 1.1 vs. 6.2 ± 1.3 days, P<0.001), drainage duration (3.8 ± 0.5 vs. 4.4 ± 0.7 days, P<0.001), and hospital stay (9.3 ± 1.8 vs. 11.1 ± 2.2 days, P<0.001) were all significantly improved in the transmediastinal esophagectomy group. The incidence of Clavien–Dindo grade ≥III complications was lower (7.6% vs. 16.0%, P=0.043), particularly pneumonia (7.6% vs. 18.2%, P=0.009) and recurrent laryngeal nerve injury (4.6% vs. 11.7%, P=0.031). Lymph node harvest was comparable (21.4 ± 6.2 vs. 22.1 ± 5.9, P=0.344). Three-month quality-of-life scores were higher in the transmediastinal esophagectomy group for global health (73.4 ± 12.1 vs. 66.5 ± 13.4, P=0.005), physical functioning (78.2 ± 11.8 vs. 70.6 ± 13.6, P=0.008), and role functioning (72.1 ± 14.2 vs. 64.3 ± 15.1, P=0.011). The 6-month DFS rates were similar between groups (93.1% vs. 91.2%, log-rank P=0.327).ConclusionsThoraco-laparoscopic transmediastinal esophagectomy is a safe, effective, and minimally invasive alternative to the McKeown approach in selected esophageal squamous cell carcinoma patients. It provides superior perioperative outcomes and enhanced recovery without compromising short-term oncologic efficacy.